MAKNA SIMBOLIK KOSTUM KESENIAN JURIG SARENGSENG DI DESA BINANGUN KOTA BANJAR - Fahmi Firdaus; Asep Wasta; Wan Ridwan Husen (Magelaran: Jurnal Pendidikan Seni, 2021)
The research entitled the Symbolic Meaning of the Jurig Sarengseng Costume in Binangun Village, Banjar City is based on the background that the City of Banjar has various cultures that are almost the same as the culture of Central Java because it is on the border of the region. One of the arts that is interesting to examine is the Jurig Sarengseng Art in Binangun Village, Banjar City because it is seen from the costumes that it seems distorted and different from other arts. This research is limited to the form of presentation and symbolic meaning of the Jurig Sarengseng Costume Art in Binangun Village, Banjar City. Based on the background of the problem above, the problem can be formulated as follows: 1). What about the costumes from Jurig Sarengseng art in Binangun Village, Banjar City?, 2). What is the symbolic meaning contained in the costume for the Jurig Sarengseng Art costume in Binangun Village, Banjar City? This study uses the qualitative analysis method. As a form of qualitative research, this study seeks to apply existing theories to explain the phenomena that occur in the object of the research material. Descriptive method in the sense that the data collected is manifested in the form of information / description about events or activities that are comprehensive, contextual, and meaningful. Data obtained from in-depth interviews with related parties.